The Effects of Consumer Trust and Satisfaction on Consumer Social Commerce Adoption in Rural Areas - Kadop , Sinthia Selvester; Yansen, Eddy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study investigates consumer purchase intention in social media commerce, particularly within the social media fashion business in rural area. That with limitation and geographical challenge, isolated rural area consumer experience more expensive shipment cost, and higher uncertainty of goods delivery. Consumer adoption of social media commerce for online purchase might involve higher trust level compare to cities area with better logistic infrastructure. Following the collection of valid data from 122 respondents in Papua, an analysis was done to determine its overall reliability, discriminant validity, structural model analysis, path coefficients and t-statistics, and Importance-Performance Matrix Analysis with PLS-SEM method. Consumer trust is significant in the context of consumer social media adoption in Papua, followed by consumer satisfaction, both of which positively influence perceived ease of use and perceived usefulness. The outcome demonstrates that consumers' trust and satisfaction in rural area are importance factors that affect consumer adoption of social media commerce and should be broadened in order to maintain the firm competitiveness for long terms.